1993
DOI: 10.1128/aem.59.1.250-254.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the structural gene encoding a copper-containing nitrite reductase and homology of this gene to DNA of other denitrifiers

Abstract: A copper-containing nitrite reductase gene (nirU) from Pseudomonas sp. strain G-179 was found in a 1.9-kb EcoRI-BamHI DNA fragment. The coding region contained information for a polypeptide of 379 amino acids. The encoded protein had 78% identity in amino acid sequence to the nitrite reductase purified from Achromobacter cycloclastes. The ligands for type 1 copper-and type 2 copper-binding sites found in A. cycloclastes were also found in Pseudomonas sp. strain G-179, suggesting that these binding sites are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 28 publications
(31 reference statements)
0
32
0
1
Order By: Relevance
“…The exchange of water oxygen with nitrite and nitric oxide has been demonstrated for some denitrifying bacteria [Garber and Hollocher, 1982;Ye et al, 1991;Shearer and Kohl, 1988], but the degree of exchange varies greatly among bacterial strains and may be related to biochemistry of nitrite reduction [Ye et al, 1991]. Bacteria possessing the heme-type nitrite reductase, as Pseudomonas chlororaphis does [Ye et al, 1993], were shown to catalyze relatively large amounts of exchange (39 -76%) [Ye et al, 1991], while Pseudomonas aureofaciens, known to possess the copper-type nitrite reductase [Glockner et al, 1993] was shown to cause relatively little incorporation of oxygen atoms from water into N 2 O (around 6%) [Ye et al, 1991]. Casciotti et al [2002] recently reported the low incorporation of oxygen isotopes of water into the N 2 O by Pseudomonas aureofaciens: While in some cases up to 10% of oxygen in N 2 O originated from water, in most cases incorporation was frequently less than 3%.…”
Section: Possible Limitations Of 18 O Applicationmentioning
confidence: 99%
“…The exchange of water oxygen with nitrite and nitric oxide has been demonstrated for some denitrifying bacteria [Garber and Hollocher, 1982;Ye et al, 1991;Shearer and Kohl, 1988], but the degree of exchange varies greatly among bacterial strains and may be related to biochemistry of nitrite reduction [Ye et al, 1991]. Bacteria possessing the heme-type nitrite reductase, as Pseudomonas chlororaphis does [Ye et al, 1993], were shown to catalyze relatively large amounts of exchange (39 -76%) [Ye et al, 1991], while Pseudomonas aureofaciens, known to possess the copper-type nitrite reductase [Glockner et al, 1993] was shown to cause relatively little incorporation of oxygen atoms from water into N 2 O (around 6%) [Ye et al, 1991]. Casciotti et al [2002] recently reported the low incorporation of oxygen isotopes of water into the N 2 O by Pseudomonas aureofaciens: While in some cases up to 10% of oxygen in N 2 O originated from water, in most cases incorporation was frequently less than 3%.…”
Section: Possible Limitations Of 18 O Applicationmentioning
confidence: 99%
“…Denitri¢cation DNA probes were derived from plasmid pnir9 for nirS [13], plasmid pRTC19 for nirK [14] and plasmid pMW12 for nosZ [15]. Genomic DNAs from P. stutzeri ATCC 14405 (nirS) and A. cycloclastes ATCC 21921(nirK) were also used as positive controls for the colony hybridization experiments.…”
Section: Ampli¢cation Puri¢cation Sequencing and Labeling Of Gene Pmentioning
confidence: 99%
“…Hydropathy analysis ( Figure 2B) and sequence comparisons ( Figure 3A) indicate that R. sphaeroides NapE is a single transmembrane polypeptide which shows high similarity to T. pantotropha NapE (55 % identity) [5] and to the product of an ORF that is divergently transcribed from the Pseudomonas sp. nirU gene encoding the copper nitrite reductase (49 % identity) [36]. NapE and NapK do not show significant similarity to each other at the amino acid sequence level but they share some properties ( Table 2).…”
Section: E Coli Yhjkmentioning
confidence: 99%